The species-level microbiota of healthy eyes revealed by the integration of metataxonomics with culturomics and genome analysis - Dong, Kui; Pu, Ji; Yang, Jing; Zhou, Guohong; Ji, Xuan; Kang, Zhiming; Li, Juan; Yuan, Min; Ning, Xiaoling; Zhang, Zhaoxia; Ma, XingYu; Cheng, Yanpeng; et al. (Frontiers in Microbiology, 2022)
Objectives To characterize the healthy ocular surface microbiota at the species level, including cultured and uncultured taxa. Methods We integrated the metataxonomic method with culturomics and genome sequencing analysis of selected isolated strains to better illustrate the taxonomic structure of the ocular surface microbiota. The metataxonomics used the full-length 16S rRNA gene sequences and the operational phylogenetic unit strategy, which can precisely identify the cultured and uncultured or potentially new taxa to species level based on the phylogenetic tree constructed. Results We detected 1,731 operational phylogenetic units (OPUs) in 196 healthy eyes from 128 people, affiliated to 796 cultured species, 784 potentially new species, and 151 potentially new higher taxa. The microbiota for each eye had 49.17 ± 35.66 OPUs. Of the 796 cultured species, 170 (21.36%) had previously caused clinical infections. Based on where they were initially isolated, the ocular surface microbiota mainly came from human body sites (34.55%), the environment (36.93%), plants (9.05%), animals (4.90%), and others; 428 strains were isolated from 20 eyes, affiliated to 42 species, and had come from the environment (33.33%) and the skin (16.67%). Of these, 47.62% had previously caused clinical infections. Genome analysis of 73 isolators revealed that 68.5% of them carried antibiotic resistance genes. The most frequently isolated genera, namely Staphylococcus, Streptococcus, and Moraxella, had an average of 5.30, four, and three resistance genes per strain, respectively. Discussion The study found that the ocular surface microbiota mainly came from the environment, plants, animals, food, and human body sites such as the skin, oral cavity, upper respiratory tract, etc. No core member of ocular surface microbiota was detected at the species level. The human eyes were invaded and colonized by bacteria from the exposed environment, some of which were capable of causing infections in humans and carried antibiotic resistance genes. Preventive measures should be developed to protect our eyes from danger.